Obtencion de un biopreparado fluido de bacillus thuringiensis - Fernandez Larrea, O.=700 1 Diaz, A.; Laguardia, E.; Calderon, A.
(Es, En)
Ilus., 14 ref.
Keywords: BACILLUS THURINGIENSIS; PRECIPITACION QUIMICA; CUBA; BIOPREPARADO